Sistemas de apoio à decisão para projecto e análise de funcionamento de sistemas de rega sob pressão (rega localizada) - Pedras, Celestina M. G. (2003)
Microirrigation is becoming popular due to recognized capabilities for providing higher water productivity of irrigation, reduced water demand when compared with other methods, low labour requirements, and improved control of environmental impacts of irrigation.